2016
DOI: 10.1021/jacs.6b01929
|View full text |Cite
|
Sign up to set email alerts
|

Concerted Growth and Ordering of Cobalt Nanorod Arrays as Revealed by Tandem in Situ SAXS-XAS Studies

Abstract: The molecular and ensemble dynamics for the growth of hierarchical supercrystals of cobalt nanorods have been studied by in situ tandem X-ray absorption spectroscopy-small-angle X-ray scattering (XAS-SAXS). The supercrystals were obtained by reducing a Co(II) precursor under H2 in the presence of a long-chain amine and a long-chain carboxylic acid. Complementary time-dependent ex situ TEM studies were also performed. The experimental data provide critical insights into the nanorod growth mechanism and unequivo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
53
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 33 publications
(54 citation statements)
references
References 75 publications
1
53
0
Order By: Relevance
“…To more specific, copper has a coordination number of 3.4 for Cu@CoS x , which is much lower than that (a coordination number of 12) for bulk copper (Table S2, Supporting Information). This result, together with several previously reported works, indicates copper species in Cu@CoS x are present in the form of sub‐nanometric metal clusters, and during the deposition of CoS x film on CF, some Cu atoms must self‐diffuse from the CF into the as‐formed CoS x film. Based on recent experimental and theoretical works on the surface properties of metallic copper, the occurrence of Cu atoms' self‐diffusion for the formation of Cu@CoS x is proposed to be mainly because (i) copper has a weak cohesive energy that makes copper surface reconstruction and atom transfer very easy and (ii) the copper surface reconstruction and atom transfer could be significantly promoted by some polar surface adsorbate molecules and ions.…”
supporting
confidence: 81%
“…To more specific, copper has a coordination number of 3.4 for Cu@CoS x , which is much lower than that (a coordination number of 12) for bulk copper (Table S2, Supporting Information). This result, together with several previously reported works, indicates copper species in Cu@CoS x are present in the form of sub‐nanometric metal clusters, and during the deposition of CoS x film on CF, some Cu atoms must self‐diffuse from the CF into the as‐formed CoS x film. Based on recent experimental and theoretical works on the surface properties of metallic copper, the occurrence of Cu atoms' self‐diffusion for the formation of Cu@CoS x is proposed to be mainly because (i) copper has a weak cohesive energy that makes copper surface reconstruction and atom transfer very easy and (ii) the copper surface reconstruction and atom transfer could be significantly promoted by some polar surface adsorbate molecules and ions.…”
supporting
confidence: 81%
“…Figure presents the modified catalysts obtained by heating four mixtures of [Co{N(SiMe 3 ) 2 } 2 (thf)], HDA, LA, and 15 % Co/Al 2 O 3 –SiO 2 in toluene at 110 °C under 3 bars of H 2 for 24 h. In these mixtures the Co/HDA/LA ratio has been varied, keeping the Co concentration constant. Although Co NRs can normally grow from a solution containing Co, HDA, and LA in a molar ratio of 1:1.7:1.2 (Co/HDA/LA) in the absence of any support, it can be seen from Figures a–d that in the presence of the 15 % Co/Al 2 O 3 –SiO 2 catalyst, it was necessary to increase the amount of ligands, and particularly that of LA, to obtain quantitatively anisotropic nano‐objects (NRs/NWs). This is attributed to the adsorption of part of the ligands on the 15 % Co/Al 2 O 3 –SiO 2 catalyst, which modifies the Co/HDA/LA ratio in the solution and affects the shape of the growing nano‐objects.…”
Section: Resultsmentioning
confidence: 99%
“…1c) and nanowires were successfully obtained by decomposition of a pre-synthesized olenic complex [Co(h 3 -C 8 H 13 )(h 4 -C 8 H 12 )] or by reduction of [Co{N(SiMe 3 ) 2 } 2 (thf)] in anisole under a pressure of 3 bar H 2 in the presence of alkylamines and carboxylic acids as ligands. 51,52 Cormary et al have conducted a beautiful time dependent in situ X-ray absorption (XAS) study to follow the evolution of both the oxidation state and coordination environment of these precursors over the course of the reaction. 52 These data suggested that the starting precursor rapidly exchanges ligands to the mixture of alkylamines before getting reduced by the hydrogen.…”
Section: Shape Control In Non-noble Metal Nanocrystalsmentioning
confidence: 99%
“…51,52 Cormary et al have conducted a beautiful time dependent in situ X-ray absorption (XAS) study to follow the evolution of both the oxidation state and coordination environment of these precursors over the course of the reaction. 52 These data suggested that the starting precursor rapidly exchanges ligands to the mixture of alkylamines before getting reduced by the hydrogen. Unfortunately, the dramatic differences in timescale between the laboratory and in situ XAS synthesis did not allow the correlation of the reduction with the nanorod growth.…”
Section: Shape Control In Non-noble Metal Nanocrystalsmentioning
confidence: 99%